Berberine as a potential autophagy modulator - Mohammadinejad, Reza; Ahmadi, Zahra; Tavakol, Shima; Ashrafizadeh, Milad (Journal of cellular physiology, 2019)
Today, pharmacognosy is considered a valuable science in the prevention and treatment of diseases. Among herbals, Berberine is an isoquinoline alkaloid found in the Berberis species. Surprisingly, it shows antimicrobial, antiviral, antidiarrheal, antipyretic, and anti‐inflammatory potential. Furthermore, it diminishes drug resistance in cancer therapy and enhances tumor suppression in part through autophagy and cell cycle arrest mechanisms. In the present review, we discuss the effect of berberine on diverse cellular pathways and describe how berberine acts as an autophagy modulator to adjust physiologic and pathologic conditions and diminishes drug resistance in cancer therapy. Among herbals, Berberine is an isoquinoline alkaloid found in the Berberis species. Furthermore, it diminishes drug resistance in cancer therapy and enhances tumor suppression in part through autophagy and cell cycle arrest mechanisms.